Biocompatibility and cellular uptake mechanisms of poly(N-isopropylacrylamide) in different cells. (January 2017) - Guo, Zhong; Li, Sha; Wang, Changyong; Xu, Jiake; Kirk, Brett; Wu, Jianping; Liu, Zonghua; Xue, Wei
Thermosensitive poly( N -isopropylacrylamide) is widely used in various biomedical applications including drug delivery systems, gene delivery systems, switching devices, sensors, and diagnostic assays. To promote these clinical applications, it is essential to have a comprehensive understanding of the biosafety of poly( N -isopropylacrylamide) and the interaction of poly( N -isopropylacrylamide) with different cell lines, which has little research until now. In this work, we evaluated the biocompatibility of poly( N -isopropylacrylamide) including cell viability, nitric oxide production, and apoptosis of macrophages RAW264.7, human bronchial epithelial cells, A549, and human umbilical vein endothelial cells in the presence of poly( N -isopropylacrylamide). We have also examined the cellular uptake mechanisms of poly( N -isopropylacrylamide) using endocytic inhibitors and insighted into the intracellular co-localization of poly( N -isopropylacrylamide) using confocal laser scanning microscope. The results showed that poly( N -isopropylacrylamide) had good biocompatibility and could be internalized by these cells. It is macropinocytosis that poly( N -isopropylacrylamide) could be internalized in RAW264.7 cells and caveolae-mediated endocytosis in human bronchial epithelial cells, A549, and human umbilical vein endothelial cells. In addition, we also evidenced that intracellular poly( N -isopropylacrylamide) was co-localized with lysosome. The study provided important information for the development and clinical applications of poly( N -isopropylacrylamide) in the biomedical field.